ANALISIS KEBERLANJUTAN PEMANFAATAN KEPITING BAKAU DI PESISIR KABUPATEN PANGKAJENE DAN KEPULAUAN - Alfira, Rizky; Djafar, Syahrul; Ilmiah, Ilmiah (Universitas Negeri Makassar, 2018)
Scylla serrata is a type of crab that lives in the mangrove forest. S. serrata is an export commodity besides Portunus pelagicus and became an important fishery commodity in Indonesia since 1980 which was obtained from catching natural stocks in coastal waters, especially in mangrove or estuary areas, and from cultivation result of brackish water. One of the human activities in the coastal region of Pangkajene and Kepulauan Islands is the catching and cultivation of mangrove crabs that contribute to the income.The study was conducted from December 2017 to January 2018,intend to find out the sustainability status of mangrove crabs utilization in Pangkajene and Kepulauan Coastal Areas. Data collection through field surveys, interviews using questionnaires and literature studies. Data analysis using fishery resource sustainability analysis through Rapfish(Rapid Appraisal for Fisheries).The result of the research shows the sustainability status of mangrove shrimp utilization in Pangkajene and Kepulauan regency in terms of ecology dimension with ordination value 79,65 and economic dimension with ordination value 96,08 is good category of sustainability, social culture dimension with ordination value 68,51; dimensions of technology with 64.53 ordination values; institutional and legal dimension with ordination value 54.15 is enough category, so that stakeholders in this case need the central, provincial, and local government on the socio-cultural, technological, institutional and legal aspects for sustainability status of mangrove crab utilization in Coastal Pangkajene Regency and Island.